Fiber-reinforced autoclaved aerated concrete board and its application
By using fibers to replace steel bars in autoclaved aerated concrete slabs and combining active excitants, the problems of steel bar corrosion, low production efficiency and poor durability are solved, and the mechanical properties of the plates are improved and maintenance costs are reduced.
Patent Information
- Application Number
- CN202510046010.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-01-13
AI Technical Summary
The existing autoclaved aerated concrete slabs with built-in reinforced mesh have problems such as steel bar corrosion, low production efficiency, high cost, poor durability and prone to mildew during the manufacturing, use and maintenance process.
By replacing traditional structural steel bars with active excitants, the fibers are evenly dispersed inside the concrete slab, thereby enhancing the mechanical properties, anti-mold properties and anti-alkali properties of the sheet.
The problem of steel bar corrosion caused by cutting is eliminated, which significantly improves production efficiency, reduces costs, improves the overall quality and service life of the board, and reduces the cost of later maintenance.
Smart Images

Figure CN119462054B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete slabs, and more specifically, relates to a fiber reinforced autoclaved aerated concrete slab and application thereof. Background Art
[0002] Traditionally, the walls of residential buildings mainly rely on traditional block materials such as red bricks. These materials are not only costly and limited in strength, but also have low construction efficiency. At the same time, they consume a lot of energy during production and use, and cause certain pollution to the environment. With the advancement of science and technology, a variety of new interior wall panels have emerged in the domestic market, such as glass fiber reinforced cement lightweight panels, fiber cement boards, autoclaved aerated concrete boards, lightweight aggregate concrete boards, wire mesh sandwich panels, gypsum boards, metal panel sandwich panels, and composite wall panels. Among these new partition wall materials, autoclaved aerated concrete boards stand out with their excellent performance and become the mainstream choice, occupying more than 60% of the market share of non-masonry applications of partition walls.
[0003] The autoclaved aerated concrete board uses cement, fly ash, aluminum powder, lime and silica sand as the main components, and is equipped with rust-proof steel bars to enhance the structural stability. This board is manufactured under high temperature and high pressure steam curing conditions to form a lightweight and porous concrete product. In the prior art, a Chinese patent with publication number CN215167134U discloses an autoclaved aerated concrete board with built-in truss steel bars, including an autoclaved aerated concrete layer and two layers of steel mesh, the two layers of steel mesh are arranged in parallel and at intervals in the autoclaved aerated concrete layer, and the autoclaved aerated concrete layer is also provided with two groups of truss steel bars, the two groups of truss steel bars are arranged in parallel between the two layers of steel mesh and along the long sides of the steel mesh, and the two layers of steel mesh are fixed to the truss steel bars on both sides; the autoclaved aerated concrete layer is also provided with two groups of steel plate profiles, the two groups of steel plate profiles are arranged in parallel between the two layers of steel mesh and along the short sides of the steel mesh, and the two layers of steel mesh are fixed to the steel plate profiles on both sides.
[0004] The above patent can increase the tensile properties of autoclaved aerated concrete panels without increasing the cross-sectional area of the reinforcement and setting up steel mesh cages, and has a low production cost; the truss steel bars and steel plate profiles are located at the edge of the autoclaved aerated concrete layer to avoid collision damage to weak parts. However, it still does not solve some problems existing in existing autoclaved aerated concrete panels with built-in steel mesh: (1) Steel bars must be added during the manufacturing process of autoclaved aerated concrete panels to enhance structural stability, which not only increases material costs, but also easily leads to the formation of gas layers due to the difference in thermal expansion coefficients between the steel bars and the slurry. This uneven gas generation phenomenon will cause uneven stress distribution inside the blank, thereby increasing the risk of board damage and affecting the overall quality; (2) Since the autoclaved aerated concrete panel has a high porosity inside, it is easy to crack due to rapid evaporation of water during maintenance. At the same time, the steel mesh has a large thermal shrinkage. The characteristics further increase the possibility of cracks and weaken the durability and stability of the board; (3) Autoclaved aerated concrete boards with added steel bars are not easy to groove and cut during construction, and the anti-rust coating on the surface of the steel bars will be damaged during the cutting process, exposing the steel bars to the air and making them easy to rust. In addition, the internal stress generated by long-term oxidation and corrosion will aggravate the cracking of the board, thereby affecting the safety and service life of the building; (4) In a high humidity environment, especially in the rainy season, autoclaved aerated concrete boards are prone to mildew and alkali efflorescence, which not only reduces the user experience, but also increases the cost and complexity of subsequent maintenance. Summary of the invention
[0005] In view of the above defects or improvement needs of the prior art, the present invention provides a fiber-reinforced autoclaved aerated concrete board and its application. By replacing traditional structural steel bars with fibers, the problem of steel bar corrosion caused by cutting can be eliminated. At the same time, since the steel mesh assembly and rust prevention processes are omitted, the production efficiency of the board can be significantly improved, and the problem of waste caused by heat shrinkage of the steel mesh can be avoided, thereby effectively reducing costs and improving actual preparation efficiency. In addition, the combination of fibers and active stimulants can ensure the uniform dispersion of fibers inside the blank, thereby achieving enhanced concrete slab mechanical properties, mildew resistance and anti-alkali performance, comprehensively improving the overall quality of the product, and significantly reducing subsequent maintenance costs.
[0006] In order to achieve the above object, the present invention provides a fiber-reinforced autoclaved aerated concrete board, comprising the following raw materials by weight: 10-15 parts of quicklime, 60-80 parts of sand, 3-5 parts of gypsum, 15-25 parts of cement, 0.25-0.5 parts of fiber, 0.04-0.1 parts of aluminum powder, 180-250 parts of water, and 0.1-0.25 parts of an active activator;
[0007] The active stimulant is mainly composed of sodium butylnaphthalene sulfonate, sulfamethoxazole, sodium dodecyl sulfate, polycarboxylate water reducer and graphite, wherein, by weight: 8-10 parts of sodium butylnaphthalene sulfonate, 4-5 parts of sulfamethoxazole, 17-20 parts of sodium dodecyl sulfate, 6-8 parts of polycarboxylate water reducer, and 25-30 parts of graphite;
[0008] The concrete slab is a plain concrete slab without steel bars.
[0009] Furthermore, the effective calcium oxide content in the quicklime should be >80%, the magnesium oxide content <5%, the undigested residue ≤8%, and meet the following performance indicators: digestion time >15min, digestion temperature >90°C, and initial heating time >5min.
[0010] Furthermore, in the cement: the CaO content is ≥60%, and the free CaO content is ≤1.5%; the NaCl and KCl contents are both less than 1.5%; the specific surface area is 250-350m 2 / kg; Among the setting time parameters, the initial setting time is 1-3h and the final setting time is 3-6h.
[0011] Furthermore, the cement is a single type of cement rather than a composite cement.
[0012] Furthermore, the gypsum is desulfurized gypsum, and the content of the main chemical component CaSO4•2H2O is >70%.
[0013] Furthermore, the fiber includes at least one of PTFE fiber and basalt fiber, and has a length of 0.1-20 mm.
[0014] Furthermore, the fiber also includes at least one of modified PTFE fiber and modified basalt fiber.
[0015] The modification methods include: surface modification or composite modification.
[0016] Furthermore, the aluminum powder has: a metallic aluminum content of >85%; an active aluminum content of >90%; a fineness standard of 3.0% or less of the residue passing through a 0.075 mm sieve hole; and a gas evolution rate of 50% or more in 4 minutes, 80% or more in 16 minutes, and 90% or more in 30 minutes.
[0017] Furthermore, the sodium butylnaphthalenesulfonate is in powder form, has a moisture content of ≤5%, and a pH value of 7-8.5 in a 1% aqueous solution.
[0018] Furthermore, the sulfamethoxazole is industrial grade sulfamethoxazole, and its purity is ≥98%.
[0019] Furthermore, the content of sodium dodecyl sulfate is ≥94%, and the pH value of the 1% aqueous solution is 7.5-9.5.
[0020] Furthermore, the polycarboxylate water-reducing agent is in powder form, has a Cr content of ≤0.20%, a NaSO4 content of <4.0%, a sum of Na2O and K2O contents of <2.0%, a cement paste fluidity of ≥240 mm, and a mortar water reduction rate of >20%.
[0021] Furthermore, the main technical parameters of the graphite soil are: powder, particle size of 6-6.5µm, purity ≥95%.
[0022] Furthermore, fly ash is used to replace part of the sand to prepare the concrete slab, and the proportion of the sand replaced by the fly ash is 10-15 parts.
[0023] Furthermore, the fly ash is directly supplied for mixing via a pipeline conveying device, or is supplied for mixing after being made into slurry by wet ash discharge.
[0024] Furthermore, the concrete slab is prepared by partially or completely replacing the sand with solid waste.
[0025] Furthermore, the solid waste includes at least one of slag, steel slag, tailings and tailings mud.
[0026] Another aspect of the present invention provides an application of a fiber-reinforced autoclaved aerated concrete slab, which is implemented by using the concrete slab as described above, wherein the concrete slab is mainly a non-load-bearing wall of a building, including an inner wall and an outer wall.
[0027] In general, the above technical solutions conceived by the present invention can achieve the following beneficial effects compared with the prior art:
[0028] 1. The concrete slab of the present invention can eliminate the problem of steel bar corrosion caused by cutting by replacing traditional structural steel bars with fibers. At the same time, since the steel mesh assembly and rust prevention processes are omitted, the production efficiency of the plate can be significantly improved, and the problem of waste caused by heat shrinkage of the steel mesh can be avoided, thereby effectively reducing costs and improving actual preparation efficiency. In addition, the combination of fibers and active stimulants can ensure the uniform dispersion of fibers inside the blank, thereby enhancing the mechanical properties, mildew resistance and anti-alkali performance of the concrete slab, comprehensively improving the overall quality of the product, and significantly reducing the subsequent maintenance costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The surface conditions of the plates of the embodiments of the present invention and the comparative examples at the end of the test are shown.
[0030] In the attached Figure 1 In the comparative example 2, the result is Figure 1 a; Comparative Example 3 results are Figure 1 b; Example 8 results are Figure 1 c; Comparative Example 4 results are Figure 1 d. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0032] Example 1
[0033] Embodiment 1 of the present invention provides a fiber-reinforced autoclaved aerated concrete board, which comprises the following raw materials by weight: 10-15 parts of quicklime, 60-80 parts of sand, 3-5 parts of gypsum, 15-25 parts of cement, 0.25-0.5 parts of fiber, 0.04-0.1 parts of aluminum powder, 180-250 parts of water, and 0.1-0.25 parts of an active activator;
[0034] The active stimulant is mainly composed of sodium butylnaphthalene sulfonate, sulfamethoxazole, sodium dodecyl sulfate, polycarboxylate water reducer and graphite, wherein, by weight: 8-10 parts of sodium butylnaphthalene sulfonate, 4-5 parts of sulfamethoxazole, 17-20 parts of sodium dodecyl sulfate, 6-8 parts of polycarboxylate water reducer, and 25-30 parts of graphite;
[0035] The concrete slab is a plain concrete slab without steel bars.
[0036] Specifically, the effective calcium oxide content in the quicklime should be >80%, the magnesium oxide content should be <5%, the undigested residue should be ≤8%, and the following performance indicators should be met: digestion time >15min, digestion temperature >90°C, and initial heating time >5min.
[0037] Preferably, the effective calcium oxide content in the quicklime is greater than 85%, thereby increasing the effective calcium content and reducing the product proportion dosage, which is used for cost control and product quality improvement;
[0038] The main technical parameters of the sand are shown in the following table:
[0039] Table 1: Main technical indicators of sand
[0040]
[0041] Table 2: Sand particle size distribution
[0042]
[0043] It should be noted that the purchased raw sand will be further processed after entering the factory to determine whether it meets the production requirements. The superior and first-class sands are treated the same way and no additional classification is required.
[0044] Preferably, the silicon content of the sand is ≥80%, which is used to improve the production quality of autoclaved aerated concrete blocks and panels;
[0045] The cement includes ordinary 42.5 grade silicate cement and meets the following technical requirements: CaO content is ≥60%, and the content of free CaO is ≤1.5%; the content of NaCl and KCl shall not exceed 1.5%; the specific surface area is 250-350m 2 / kg; in the setting time parameters, the initial setting time is 1-3h, and the final setting time is 3-6h; wherein the CaO content in the cement is ≥60%, and the free CaO content is ≤1.5%, which is used for cost control and product quality improvement;
[0046] Preferably, the cement is a single type of cement rather than a composite cement;
[0047] Preferably, the cement is used in the order in which it is put into storage, and the storage period of the cement should not exceed 3 months, and expired cement should be inspected;
[0048] The main chemical component of the gypsum, CaSO4•2H2O, has a content of >70%, which is used to regulate the gas generation process of aerated concrete, control the gas generation rate during the aluminum powder gas generation process, avoid excessive gas generation resulting in excessive or unstable bubbles, thereby affecting the pore structure and strength of the concrete, and regulate the quicklime dissolution and slurry thickening speed;
[0049] Preferably, the gypsum is desulfurized gypsum to improve the strength and durability of the concrete slab.
[0050] The fiber includes at least one of PTFE fiber (polytetrafluoroethylene fiber) and basalt fiber, which is used to be interspersed in the concrete to form a three-dimensional spatial structure, absorb and disperse stress, and improve the compressive strength and tensile strength of the board; secondly, due to the short length of the fiber, it can be well dispersed in the concrete slurry and well contacted with the interface between the concrete particles to generate mechanical bite force, and then when the concrete board is subjected to external tension, the fiber can replace the board to bear a certain tension, thereby reducing the probability of cracks, and because the fiber is randomly distributed in the board, the fiber can evenly distribute the tension along the axial direction to the adjacent, thereby relieving the concentration of stress and enhancing the toughness of the board; in addition, the fiber is evenly distributed in random directions, which appropriately blocks the disordered growth rate of the autoclaved aerated concrete in the gas generation stage and inhibits the generation of large bubbles. At the same time, the heat shrinkage performance of the fiber is similar to that of the substrate, avoiding the generation of air layers due to the shrinkage of the steel mesh in the traditional autoclaved aerated concrete board, making the board pore structure more dense and strong, and effectively improving the strength of the autoclaved aerated concrete product.
[0051] In an optional embodiment, the fiber also includes at least one of modified PTFE fiber and modified basalt fiber, which is used to cooperate with the active stimulant to further improve the performance of the concrete board and the scope of use of the product; in addition, the modification method includes: surface modification or composite modification. Among them, the surface modification method also includes: soaking the pre-modified PTFE fiber and / or basalt fiber in a 5-15% sodium hydroxide solution at room temperature for 0.5-2 hours; washing the fiber soaked in sodium hydroxide with deionized water and anhydrous ethanol for multiple times until it is washed to neutral; adding the fiber washed to neutral and γ-aminopropyl triethoxysilane coupling agent to the mixed solution of deionized water and anhydrous ethanol, stirring the mixed solution evenly and standing it for treatment; after standing, filtering the fiber and the solution; the separated fiber and water-based epoxy resin are fully stirred and dried, and then cut into short fibers with a specification of 0.1-20mm to finally obtain modified fibers. It should be noted that the pre-modified PTFE fiber is a PTFE fiber modified by filling, and the filling material is glass fiber. It is understandable that when the fiber is only PTFE fiber, due to the alkali resistance of PTFE fiber and the absence of hydroxyl groups in its structure, the PTFE fiber surface impurities and static electricity are removed by washing with deionized water and anhydrous ethanol, and then the PTFE fiber is wrapped with water-based epoxy resin to avoid agglomeration into flocculation, thereby helping to improve the performance of the autoclaved aerated concrete board prepared subsequently. In addition, in an optional embodiment, the PTFE fiber is pre-modified by a filling modification method, and the filling material is glass fiber, and then the pre-modified PTFE fiber is processed by the surface modification preparation method to obtain a finished modified PTFE fiber, thereby further improving the performance of the autoclaved aerated concrete board by increasing the friction coefficient of the PTFE fiber.
[0052] Preferably, the final length of the fiber is 0.1-20 mm, so as to improve its fluidity in the concrete slurry and make it evenly distributed in the board; secondly, to avoid the phenomenon that longer fibers are pulled out or broken during the cutting process, resulting in uneven cuts, increased burrs, etc., which affect the quality of the cut surface.
[0053] The aluminum powder can react with alkaline substances and water in the slurry to generate hydrogen during the sheet forming process, thereby improving the physical properties of the sheet. Its main technical parameters are: metal aluminum content>85%; active aluminum content>90%; fineness standard is the sieve residue passing through a 0.075mm sieve hole ≤3.0%; gas evolution rates are ≥50% in 4 minutes, ≥80% in 16 minutes, and ≥90% in 30 minutes;
[0054] The activity stimulant is mainly composed of sodium butylnaphthalene sulfonate, sulfamethoxazole, sodium dodecyl sulfate, polycarboxylic acid water reducer and graphite, wherein these materials are measured by weight: 8-10 parts of sodium butylnaphthalene sulfonate, 4-5 parts of sulfamethoxazole, 17-20 parts of sodium dodecyl sulfate, 6-8 parts of polycarboxylic acid water reducer, and 25-30 parts of graphite, which is used to improve the raw material activity, slurry workability, and gas hardening adaptability of the green body, effectively prevent the green body from settling and collapsing, and at the same time, optimize the water-cement ratio, the contact and mutual reaction between the fiber and the concrete particles, and enhance the final compressive strength of the product. In addition, the use of sulfamethoxazole in concrete slabs can effectively inhibit the mildew and alkali efflux of the board surface, especially in rainy and humid environments.
[0055] The main technical parameters of the sodium butylnaphthalenesulfonate are: powdery, moisture content ≤5%, pH value of 7-8.5 in 1% aqueous solution.
[0056] The sulfamethoxazole is industrial grade sulfamethoxazole, and its main technical parameters are: melting point>160℃, density about 1.462g / cm 3 , purity ≥98%. It should be noted that the molecular formula of sulfamethoxazole is C 10 H 11 N3O3S, with a molecular weight of 253.28 g / mol, contains a sulfonamide group (-SO2NH), a methoxazole ring (5-methyl-3-isoxazole), and a benzene ring in its structure. Due to its unique molecular structure, sulfamethoxazole has extremely low solubility in water, but can be dissolved in dilute sodium hydroxide solution and dilute acid. This property enables it to adapt well to the alkaline environment of concrete slurry and ensure uniform dispersion in the slurry, thereby performing its function more effectively.
[0057] The main technical parameters of the sodium dodecyl sulfate are: melting point 180-207°C, density 0.25g / ml, sodium dodecyl sulfate content ≥94%, and pH value of 7.5-9.5 in 1% aqueous solution.
[0058] The main technical parameters of the polycarboxylic acid water-reducing agent are: powder, Cr content ≤ 0.20%, NaSO4 content < 4.0%, the sum of Na2O and K2O content < 2.0%, cement paste fluidity ≥ 240mm, mortar water reduction rate > 20%.
[0059] The main technical parameters of the graphite soil are: powder, particle size of 6-6.5µm, purity ≥95%, density 2-2.2g / cm³.
[0060] It should be noted that, because the autoclaved aerated concrete is loose and porous inside, it is called a "breathing board", but it also makes it easy to store water vapor in the air in the pores. When the water is not removed in time and it is used directly or in a high humidity environment, it is easy to cause alkali and mildew. The chemical structure of sulfamethoxazole consists of a p-aminobenzenesulfonamide group and a 5-methylisoxazole ring, wherein the cyclic amide group and the aromatic amine group can form a binary complex through the bond bridge effect with the metal cation, increase the adsorption capacity between the sulfamethoxazole molecule and the metal ion, and form sulfamethoxazole-heavy metal crystals; this process helps to lock the metal ions in the slurry, so that the metal ions in the board are evenly distributed, and because it is almost insoluble in water, it effectively prevents the diffusion of metal ions after the board is formed, thereby avoiding the occurrence of alkali; secondly, as a broad-spectrum antibiotic, sulfamethoxazole has a stable structure, can adapt to the processing environment of autoclaved aerated concrete boards, and can continue to produce toxic inhibition effects on bacteria and / or molds after the board is formed, thereby delaying the mildew of the concrete board.
[0061] In an optional embodiment, the preparation method of the concrete slab includes the following steps: adding part of water to sand and gypsum, wet grinding and mixing to obtain slurry 1; adding fiber, cement, quicklime and active stimulant to the slurry 1, mixing to obtain slurry 2; mixing aluminum powder with part of water to form a suspension, adding the suspension to the slurry 2, mixing to obtain slurry 3; heating the slurry 3 to 40-45°C by steam, and then pouring the slurry into a mold for curing to form a green body, and during the curing process, the green body The body temperature is 70-90°C, and the curing time is 2-4h; the green body is cut, and the waste generated in the process of cutting the green body is peeled and stirred, and then the above steps are repeated; the cut green body is transported to an autoclave for steam curing, and during the steam curing process, the temperature and pressure inside the autoclave are increased for 2h, so that the temperature in the autoclave reaches 180-210°C and the pressure reaches 10-13MPa, and then the temperature and pressure are maintained at a constant temperature and pressure for 6-10h, and then the temperature and pressure are reduced to normal temperature and pressure to produce the finished concrete slab.
[0062] The concrete slab of the present embodiment replaces the traditional structural steel bars with fibers, which can eliminate the problem of steel bar corrosion caused by cutting. At the same time, since the steel mesh assembly and rust prevention processes are omitted, the production efficiency of the plate can be significantly improved, and the problem of waste caused by heat shrinkage of the steel mesh can be avoided, effectively reducing costs and improving actual preparation efficiency. In addition, the combination of fibers and active stimulants can ensure the uniform dispersion of fibers inside the blank, thereby enhancing the mechanical properties, mildew resistance and anti-alkali performance of the concrete slab, comprehensively improving the overall quality of the product, and significantly reducing subsequent maintenance costs.
[0063] Example 2
[0064] On the basis of Example 1, in Example 2 of the present invention, fly ash is used to replace part of the sand to prepare the concrete slab, and the number of sand replaced by the fly ash is 10-15 parts, which is used to reduce costs and increase efficiency while ensuring that the quality of the concrete slab meets the requirements, thereby improving the competitiveness of the enterprise.
[0065] Preferably, the main technical indicators of the fly ash are as follows:
[0066] Table 3: Main technical indicators of fly ash
[0067]
[0068] Preferably, the fly ash is directly supplied for mixing through a pipeline conveying device, or is made into a slurry through wet ash discharge and then supplied for mixing. It should be noted that when wet ash discharge is used, the water content and water weight in the wet ash need to be calculated, and the amount of water in the original components needs to be reduced.
[0069] Example 3
[0070] Based on Example 1, in Example 3 of the present invention, solid waste is used to partially or completely replace the sand to prepare the concrete slab, which is used to reduce the consumption of natural resources while ensuring that the quality of the concrete slab meets the requirements, and is helpful to process a large amount of industrial solid waste, reduce the pressure on landfills and the risk of environmental pollution, reduce costs and increase efficiency, and enhance corporate competitiveness.
[0071] Preferably, the solid waste includes at least one of slag, steel slag, tailings and tailings mud.
[0072] Example 4
[0073] On the basis of Examples 1 to 3, Example 4 of the present invention provides an application of a fiber-reinforced autoclaved aerated concrete board, which is mainly a non-load-bearing wall of a building, including interior walls and exterior walls.
[0074] Example 5
[0075] On the basis of Example 1, Example 5 of the present invention provides a fiber-reinforced autoclaved aerated concrete board, which is prepared by the preparation method in Example 1, wherein the raw materials in the concrete board are, by weight: 13 parts of quicklime, 62 parts of sand, 4 parts of gypsum, 18 parts of cement, 0.25 parts of fiber, 0.05 parts of aluminum powder, 180 parts of water, and 0.125 parts of active activator.
[0076] Example 6
[0077] Based on Example 1, Example 6 of the present invention provides a fiber-reinforced autoclaved aerated concrete board, which is prepared by the preparation method in Example 1, wherein the raw materials in the concrete board are, by weight: 15 parts of quicklime, 60 parts of sand, 5 parts of gypsum, 20 parts of cement, 0.3 parts of fiber, 0.055 parts of aluminum powder, 190 parts of water, and 0.1 parts of an active stimulant.
[0078] Example 7
[0079] Based on Example 1, Example 7 of the present invention provides a fiber-reinforced autoclaved aerated concrete board, which is prepared by the preparation method in Example 1, wherein the raw materials in the concrete board are, by weight: 15 parts of quicklime, 80 parts of sand, 3 parts of gypsum, 21 parts of cement, 0.4 parts of fiber, 0.06 parts of aluminum powder, 210 parts of water, and 0.2 parts of active activator.
[0080] Example 8
[0081] On the basis of Example 1, Example 8 of the present invention provides a fiber-reinforced autoclaved aerated concrete board, which is prepared by the preparation method in Example 1, wherein the raw materials in the concrete board are, by weight: 13 parts of quicklime, 67 parts of sand, 3 parts of gypsum, 17 parts of cement, 0.5 parts of fiber, 0.045 parts of aluminum powder, 180 parts of water, and 0.25 parts of active activator.
[0082] Comparative Example 1
[0083] On the basis of Example 1, Comparative Example 1 of the present invention provides a fiber-reinforced autoclaved aerated concrete board, which is prepared by the preparation method in Example 1, wherein the raw materials in the concrete board are calculated by weight as follows:
[0084] 15 parts of quicklime, 80 parts of sand, 3 parts of gypsum, 21 parts of cement, 0.4 parts of fiber, 0.06 parts of aluminum powder, and 180 parts of water.
[0085] In the autoclaved aerated concrete boards in Examples 5 to 8, the fibers used are modified fibers, and the active activator is a mixed material from the same batch, and these raw materials are calculated by weight: 9 parts of sodium butylnaphthalene sulfonate, 5 parts of sulfamethoxazole, 18 parts of sodium dodecyl sulfate, 6 parts of polycarboxylate water reducer, and 25 parts of graphite clay; secondly, the sizes of the finished autoclaved aerated concrete boards prepared in Examples 5 to 8 and Comparative Example 1 are all 1800mm×600mm×100mm. At the same time, the basic properties of each concrete board were tested in the laboratory using standard test methods, and the test results are shown in Table 4:
[0086] Table 4: Test results of the first batch of concrete slab samples
[0087]
[0088] It can be seen from the test results in Table 4 that the concrete slabs in the above-mentioned Examples 6 to 8 all meet the requirements for concrete slabs in national and / or industry standards, and can fully meet the various performance requirements of non-load-bearing walls of buildings, but the drying shrinkage values of the samples in Example 5 and Comparative Example 1 exceed the standard values. In particular, the concrete slabs in the four embodiments to which the active stimulant is added are significantly better than Comparative Example 1 to which the active stimulant is not added in terms of compressive strength; secondly, the addition of the active stimulant significantly improves the contribution of the fiber to the bending bearing capacity of the concrete slab. In addition, the concrete slab of Example 8 is better than the other three embodiments in both the maximum and minimum values of compressive strength, which is related to the higher proportions of sand, cement, quicklime, fiber and active stimulant in its formula. This result shows that increasing the amount of active stimulant can further promote the contact and interaction between the fiber and concrete particles, thereby effectively improving the performance of the concrete slab.
[0089] Example 9
[0090] On the basis of Example 1, Example 9 of the present invention provides a fiber-reinforced autoclaved aerated concrete board, which is prepared by the preparation method in Example 1, wherein the raw materials in the concrete board are, by weight: 13 parts of quicklime, 67 parts of sand, 3 parts of gypsum, 17 parts of cement, 0.5 parts of fiber, 0.045 parts of aluminum powder, 180 parts of water, and 0.25 parts of an active activator;
[0091] Among them, the mixed materials in the active stimulant are: 10 parts of sodium butylnaphthalene sulfonate, 5 parts of sulfamethoxazole, 20 parts of sodium dodecyl sulfate, 6 parts of polycarboxylic acid water reducer, and 30 parts of graphite clay.
[0092] Example 10
[0093] On the basis of Example 1, Example 10 of the present invention provides a fiber-reinforced autoclaved aerated concrete board, which is prepared by the preparation method in Example 1, wherein the raw materials in the concrete board are, by weight: 13 parts of quicklime, 67 parts of sand, 3 parts of gypsum, 17 parts of cement, 0.5 parts of fiber, 0.045 parts of aluminum powder, 180 parts of water, and 0.25 parts of an active activator;
[0094] Among them, the mixed materials in the active stimulant are as follows: 9 parts of sodium butylnaphthalene sulfonate, 4 parts of sulfamethoxazole, 17 parts of sodium dodecyl sulfate, 7 parts of polycarboxylic acid water reducer, and 27 parts of graphite clay.
[0095] Embodiment 11
[0096] On the basis of Example 1, Example 11 of the present invention provides a fiber-reinforced autoclaved aerated concrete board, which is prepared by the preparation method in Example 1, wherein the raw materials in the concrete board are, by weight: 13 parts of quicklime, 67 parts of sand, 3 parts of gypsum, 17 parts of cement, 0.5 parts of fiber, 0.045 parts of aluminum powder, 180 parts of water, and 0.25 parts of an active activator;
[0097] Among them, the mixed materials in the active stimulant are: 8 parts of sodium butylnaphthalene sulfonate, 5 parts of sulfamethoxazole, 19 parts of sodium dodecyl sulfate, 8 parts of polycarboxylic acid water reducer, and 25 parts of graphite clay.
[0098] Among them, the finished autoclaved aerated concrete panels prepared in the above Examples 8 to 11 and Comparative Example 1 have a size of 1800 mm×600 mm×100 mm, and the fibers are all modified fibers. At the same time, the basic properties of each concrete panel were tested in the laboratory using standard test methods. The test results are shown in Table 5:
[0099] Table 5: Test results of the second batch of concrete slab samples
[0100]
[0101] It can be seen from the test results in Table 5 that the concrete slabs in the above four embodiments all meet the requirements for concrete slabs in national and / or industry standards, and can fully meet the various performance requirements of non-load-bearing walls of buildings. In particular, taking Example 8 as a reference, by adjusting the ratio of the mixed materials in the active stimulant, the compressive strength of the concrete slabs of Examples 9 to 11 obtained is significantly higher than that of Comparative Example 1 to which no active stimulant is added. In addition, the differences between the performance parameters of the above four embodiments are not significant, which means that the different mixed material ratios of the active stimulants used in the experiment can effectively improve the performance of the concrete slabs, showing good adaptability and consistency. These results further confirm the important role and flexibility of active stimulants in improving the performance of concrete slabs.
[0102] Comparative Example 2
[0103] On the basis of Example 1, Comparative Example 2 of the present invention provides a fiber-reinforced autoclaved aerated concrete board, which is prepared by the preparation method in Example 1, wherein the raw materials in the concrete board are, by weight: 13 parts of quicklime, 67 parts of sand, 3 parts of gypsum, 17 parts of cement, 0.5 parts of fiber, 0.045 parts of aluminum powder, 180 parts of water, and 0.25 parts of an active activator;
[0104] The mixed materials in the active stimulant are as follows: 9 parts of sodium butylnaphthalene sulfonate, 0 parts of sulfamethoxazole, 18 parts of sodium dodecyl sulfate, 6 parts of polycarboxylic acid water reducer, and 25 parts of graphite clay.
[0105] Comparative Example 3
[0106] On the basis of Example 1, Comparative Example 3 of the present invention provides a fiber-reinforced autoclaved aerated concrete board, which is prepared by the preparation method in Example 1, wherein the raw materials in the concrete board are, by weight: 13 parts of quicklime, 67 parts of sand, 3 parts of gypsum, 17 parts of cement, 0.5 parts of fiber, 0.045 parts of aluminum powder, 180 parts of water, and 0.25 parts of an active activator;
[0107] Among them, the mixed materials in the active stimulant are: 9 parts of sodium butylnaphthalene sulfonate, 2 parts of sulfamethoxazole, 18 parts of sodium dodecyl sulfate, 6 parts of polycarboxylic acid water reducer, and 25 parts of graphite clay.
[0108] Comparative Example 4
[0109] On the basis of Example 1, Comparative Example 4 of the present invention provides a fiber-reinforced autoclaved aerated concrete board, which is prepared by the preparation method in Example 1, wherein the raw materials in the concrete board are, by weight: 13 parts of quicklime, 67 parts of sand, 3 parts of gypsum, 17 parts of cement, 0.5 parts of fiber, 0.045 parts of aluminum powder, 180 parts of water, and 0.25 parts of an active activator;
[0110] Among them, the mixed materials in the active stimulant are as follows: 9 parts of sodium butylnaphthalene sulfonate, 8 parts of sulfamethoxazole, 18 parts of sodium dodecyl sulfate, 6 parts of polycarboxylic acid water reducer, and 25 parts of graphite clay.
[0111] Among them, the concrete boards prepared in the above comparative examples 2 to 4 and Example 8 are all modified fibers, and the board size is 1800mm×600mm×100mm. Afterwards, the whole board is cut into test sample blocks of 200mm×100mm×100mm, and the sample blocks of the above embodiments and comparative examples are placed at 30°C and a relative humidity of 90% for 60 days, and the mildew and alkali efflorescence of each sample block are observed and recorded, wherein the initial mildew time is the initial days when mildew appears on the board surface, and the initial alkali efflorescence time is the initial days when white crystals appear on the board surface. The test results are shown in Tables 6 and Figure 1 (Comparative Example 2 results are Figure 1 a; Comparative Example 3 results are Figure 1 b; Example 8 results are Figure 1 c; Comparative Example 4 results are Figure 1 d):
[0112] Table 6: Test results of the third batch of concrete slab samples
[0113]
[0114] It can be seen from the test results in Table 6 that the sample blocks of the comparative example 2 group without sulfamethoxazole added showed mildew on the 3rd day and alkali efflorescence on the 30th day under the test conditions, and the alkali efflorescence on the surface of the sample blocks was serious when the test was stopped; the sample blocks of the comparative example 3 group with low dosage of sulfamethoxazole showed mildew on the 7th day and alkali efflorescence on the 45th day; while the sample blocks of the example 8 group with medium dosage and the sample blocks of the comparative example 4 group with high dosage both showed mildew on the 20th day, and no alkali efflorescence occurred during the test period; the above test results show that sulfamethoxazole can effectively inhibit the mildew and alkali efflorescence of the concrete slab and the effect is positively correlated with its addition amount, but when the addition amount reaches a certain amount, the effect has no significant difference, therefore, the sulfamethoxazole in the concrete slab can be appropriately adjusted according to the amount of other metal-containing raw materials to reduce the production cost.
[0115] It should be noted that in the present invention, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "includes..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0116] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Those skilled in the art will readily understand that the above are only preferred embodiments of the present invention, and are not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention shall be included within the scope of protection of the present invention.
Claims
1. A fiber-reinforced autoclaved aerated concrete board, characterized in that: The raw materials include the following by weight: 10-15 parts of quicklime, 60-80 parts of sand, 3-5 parts of gypsum, 15-25 parts of cement, 0.25-0.5 parts of fiber, 0.04-0.1 parts of aluminum powder, 180-250 parts of water, and 0.1-0.25 parts of active activator; The active stimulant is mainly composed of sodium butylnaphthalene sulfonate, sulfamethoxazole, sodium dodecyl sulfate, polycarboxylate water reducer and graphite, wherein, by weight: 8-10 parts of sodium butylnaphthalene sulfonate, 4-5 parts of sulfamethoxazole, 17-20 parts of sodium dodecyl sulfate, 6-8 parts of polycarboxylate water reducer, and 25-30 parts of graphite; The concrete slab is a plain concrete slab without reinforcement.
2. The concrete slab according to claim 1, characterized in that The quicklime should have an effective calcium oxide content of >80%, a magnesium oxide content of <5%, undigested residue ≤8%, and meet the following performance indicators: digestion time >15min, digestion temperature >90°C, and initial heating time >5min.
3. The concrete slab according to claim 1, characterized in that The cement has a CaO content of ≥60% and a free CaO content of ≤1.5%; the NaCl and KCl contents are both less than 1.5%; and a specific surface area of 250-350m 2 / kg; Among the setting time parameters, the initial setting time is 1-3h and the final setting time is 3-6h.
4. The concrete slab according to claim 3, characterized in that The cement described is a single type of cement, not a composite cement.
5. The concrete slab according to claim 1, characterized in that The gypsum is desulfurized gypsum, and the content of the main chemical component CaSO4•2H2O is >70%.
6. The concrete slab according to claim 1, characterized in that The fiber includes at least one of PTFE fiber and basalt fiber, and has a length of 0.1-20 mm.
7. The concrete slab according to claim 6, characterized in that The fiber also includes at least one of modified PTFE fiber and modified basalt fiber, The modification methods include: surface modification or composite modification.
8. The concrete slab according to claim 1, characterized in that The aluminum powder has: a metal aluminum content of >85%; an active aluminum content of >90%; a fineness standard of 3.0% or less of the residue passing through a 0.075 mm sieve hole; and gas evolution rates of 50% or more in 4 minutes, 80% or more in 16 minutes, and 90% or more in 30 minutes.
9. The concrete slab according to claim 1, characterized in that The sodium butylnaphthalenesulfonate is in powder form, with a moisture content of ≤5% and a pH value of 7-8.5 in a 1% aqueous solution.
10. The concrete slab according to claim 1, characterized in that The sulfamethoxazole is industrial grade sulfamethoxazole, and its purity is ≥98%.
11. The concrete slab according to claim 1, characterized in that The content of sodium dodecyl sulfate is ≥94%, and the pH value of a 1% aqueous solution is between 7.5 and 9.
5.
12. The concrete slab according to claim 1, characterized in that The polycarboxylate water-reducing agent is in powder form, with a Cr content of ≤0.20%, a NaSO4 content of <4.0%, a sum of Na2O and K2O contents of <2.0%, a cement paste fluidity of ≥240 mm, and a mortar water reduction rate of >20%.
13. The concrete slab according to claim 1, characterized in that The main technical parameters of the graphite soil are: powder, particle size of 6-6.5µm, purity ≥95%.
14. The concrete slab according to any one of claims 1 to 13, characterized in that The concrete slab is prepared by replacing part of the sand with fly ash, and the proportion of the sand replaced by the fly ash is 10-15 parts.
15. The concrete slab according to claim 14, characterized in that The fly ash is directly supplied for mixing through a pipeline conveying device, or is supplied for mixing after being made into slurry through wet ash discharge.
16. The concrete slab according to any one of claims 1 to 13, characterized in that The concrete slab is prepared by partially or completely replacing the sand with solid waste.
17. The concrete slab according to claim 16, characterized in that The solid waste includes at least one of slag, steel slag, tailings and tailings mud.
18. An application of a fiber reinforced autoclaved aerated concrete board, which is realized by using the concrete board according to any one of claims 1 to 17, characterized in that: The concrete slabs are mainly non-load-bearing walls of buildings, including interior walls and exterior walls.
Citation Information
Patent Citations
Autoclaved aerated concrete slab with built-in truss steel bars
CN215167134U
Preparation method and application of fiber-reinforced autoclaved aerated concrete slab
CN119430839A